The influence of celebrity endorsement in social media instagram on attitude towards brand and brand image to customer purchase intention - Fatiha Rahmalina Fitri (Jurnal Akuntansi, Manajemen dan Ekonomi, 2018)
Social media Instagram become a platform that give chance for business actors, because Instagram is the most popular social media used in Indonesia. One of fashion industries in Indonesia, Rubylicious, take this opportunity to market the products through social media Instagram. Rubylicious embrace one of influencers in Instagram; Ayudia Bing Slamet as its endorser for Rubylicious brand. This research was conducted to analyze the indicators of celebrity endorsement (credibility, attractiveness, familiarity, & match-up congruence), attitude towards brand, brand image, to purchase intention. The research methodology used for this study is a case study with survey research method. Convenience sampling technique derived from non-probability sampling techniques are used for sample selection. The sample of this research is 175, from people who know the existance of Rubylicious and Ayudia Bing Slamet. Statistical software SPSS and AMOS is used to analyze the data. The research has implications for Rubylicious and other marketers; they can consider some factors needed of celebrity to endorsement strategy. The limitation of this research is some of answers less contributed to explain respondents’ perception clearly.